2019
DOI: 10.3171/2018.6.jns18467
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral progression after unilateral evacuation of bilateral chronic subdural hematomas: the volume relation ratio as prognostic factor?

Abstract: OBJECTIVEUnilateral evacuation of bilateral chronic subdural hematomas (bcSDHs) is associated with higher retreatment rates than an initial bilateral intervention. One reason for that is a possible progression in the size of the contralateral side after unilateral treatment. Thus, the authors focused their study on finding predictors of the need for contralateral retreatment.METHODSAll patients who had undergone unilateral or bilateral evacuation of bcSDHs in the Department of Neurosurgery at the University Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…There’s also evidence pointing to the minicraniotomy having a place in the treatment of recurrent more organised CSDHs [ 2 , 13 , 18 , 25 ]. Identical recurrence rates have been described previously in other studies [ 3 , 19 ]. It is also important to note that intuitively, the reoperation rate of bCSDH will be higher compared to unilateral CSDH since there are two CSDHs.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…There’s also evidence pointing to the minicraniotomy having a place in the treatment of recurrent more organised CSDHs [ 2 , 13 , 18 , 25 ]. Identical recurrence rates have been described previously in other studies [ 3 , 19 ]. It is also important to note that intuitively, the reoperation rate of bCSDH will be higher compared to unilateral CSDH since there are two CSDHs.…”
Section: Discussionsupporting
confidence: 84%
“…Our study confirms and is in line with the results observed in the Danish study with unilateral evacuation of bCSDH significantly increasing the risk of reoperation. Our study is to our knowledge the largest retrospective study which has investigated bCSDH concerning the reoperation rate with respect to the choice of surgical approach [ 3 , 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recently published articles studying the results of unilateral surgical evacuation in bCSDH 25,26 comprising a total of 394 cases stated that currently the decision to perform a unilateral evacuation on bCSDH is based on the relative volume of each subdural collection and in the presence of lateralizing clinical signs. The unilateral procedure in bCSDH was found in these studies, to be an independent risk factor for reoperation, a fact that led these authors to recommend the bilateral evacuation from the start.…”
Section: Discussionmentioning
confidence: 99%